Specialised impounding plan of a rockfill dam after construction case study of Madani dam - Farajniya, Rasoul; Poursorkhabi, Ramin Vafaei (Geotechnical research, 2025)
To control and ensure the safety of the Madani Tabriz dam at the period 10 years after the end of construction, dam monitoring is performed utilising data from the instrumentation installed on the dam’s body. In this study, using the Midas finite element software, the results of the settlement, pore water pressure, and total stress of the Madani rockfill dam were calculated 10 years after the end of construction of the dam body and compared with the results of the instrumentation observation. The linear correlation coefficients between the data obtained from the sensors and the numerical analysis results for the items of settlement, pore water pressure, and total stress are 84%, 67%, and 99%, respectively. Sensitivity analyses were carried out for present special impounding programme for the dam, with controlling two simultaneous items: the pore water pressure and effect stress changes in the clay core, with 10 years passed since the completion of construction of the dam body. While controlling the reliability coefficient of the body stability, with a 30 cm/d reservoir impounding, the dam reservoir will be filled in 80 d. Suggest an impounding program for a reservoir behind an earth or rockfill dam, detailing a specific plan that ensures all safety aspects of the dam are controlled.